العيش المشترك والتنوع الثقافي عند كلود ليفي شتراوس (El-Wahat Journal for Research and Studies, 2025)
Living Harmoniously With And For Others, Devoid Of Racism And Ethnic Prejudices Within Cultural And Civilizational Classifications, Constituted Claude Lévi-Strauss's Pivotal Pursuit. His Aim Was To Actualize The Principle Of Cultural And Civilizational Equity, Surmounting Historical Categorization Hurdles And Eliminating Exclusions That Branded Indigenous Populations As Uncivilized And Uncultured. Anthropologically, Lévi-Strauss Acknowledged The Significance Of The "Other," Fostering Impartiality, Cultural Parity, And Shared Coexistence. He Transcended Ethnic And Civilizational Divides, Dismantling The Binary Of Civilized And Primitive Societies. He Postulated That Civilization Isn't Exclusive To Modern Times But Inherent To All Societies, Each Possessing A Distinct Logic. Moreover, Lévi-Strauss Extended His Transcendence To Cultural Values, Championing Diversity And The Multitude Of Civilizational Principles Through The Tenet Of Communal Living, Where Humanism Prevails Over Racial, Historical, Economic, And Political Biases. Key Words: Collective Living , Culture, Structuralism Anthropology, Peace.